Pengaruh kekhusyukan Shalat untuk Meningkatkan Kesejahteraan Psikologis (Psychological Well Being) pada Mahasiswa Kampus V Bukittinggi Universitas Negeri Padang - Syahidah Alifia; Aggio Malvino; Geni Novella; Muhammad Ikhwanurrahim; Qonita Rohima; Rani Sagita; Shakira Ghaniya Irhamni (KAMPUS AKADEMIK PUBLISING, 2026)
The purpose of this study was to determine whether there was an influence of prayer solemnity to improve psychological well being in Campus V Bukittinggi Students of Padang State University. This study used a quantitative approach using survey methods. The research design used was correlational research and data analysis using simple regression analysis. The number of samples in this study was 112 people. The sampling technique used is a purposive sampling technique. The data collection of this study used a scale technique using Likert answer examples. This study used 2 measurement scales, namely the prayer solemnity scale and the psychological well being scale. The prayer solemnity scale consists of 35 items, and the psychological well being scale consists of 36. The results of the analysis showed that there was an effect of prayer solemnity on psychological well being (p = 0.000; p < 0.05). The solemnity of prayer also has a unidirectional and positive relationship to psychological well-being, where the R-square value from the summary model of a simple regression analysis test produces an R-square value of 0.273 which shows that prayer solemnity have effect to improve psychological well being by 27.3%. The results of the regression analysis resulted in a constant value (A) of 64.695, while the value of the regression coefficient (B) of emotional intelligence was 0.210.